Experiences in Conducting Participatory Communication Research for HIV Prevention Globally: Translating Critical Dialog into Action through Action Media - Parker, Warren Martin; Becker-Benton, Antje (Frontiers in Public Health, 2016)
Problem: Developing communication to support health and wellbeing of vulnerable communities requires a multifaceted understanding of local perspectives of contextual challenges and potentials for change. While participatory research enhances understanding, robust methodologies are necessary to translate emerging concepts into viable communication approaches. Communicators and change agents need to clarify pathways for change, barriers and enablers for change, as well as the role, orientation and content of communication to support change. While various approaches to participatory action research with vulnerable communities have been developed, there is a dearth of methodologies that address the formulation of communication concepts that can be applied at scale. Methods: The Action Media methodology has been refined over a period of two decades, being applied to addressing HIV, related aspects such as gender-based violence, as well as broader issues such as maternal and child health, sanitation and malaria in Africa, The Caribbean and Asia. The approach employs a sequence of interactive sessions involving communicator-researchers and participants from one or more communities that face social or health challenges. Sessions focus on understanding audiences through their engagement with these challenges and leading to shaping of relevant communication concepts that can be linked to mobilization for change. Results: The Action Media methodology contributes to processes of shared learning linked to addressing social and health challenges. This includes including determining priorities, identifying barriers and facilitators for change, understanding processes of mobilizing knowledge in relation to context, determining appropriate communication approaches, and integrating indigenous language and cultural perspectives into communication concepts. Emerging communication strategies include support to systematic action and longer-term mobilization. Recommendations: Communication to address public health concerns is typically developed through expert-led didactic approaches that, at best, engage audiences at the end the development cycle through pre-testing of communication concepts. Action Media provides an alternative approach that can be utilized to inform communication by integrating community perspectives at the outset. Notwithstanding the focused engagement with small groups representative of health-vulnerable sub-populations, Action Media findings have informed large-scale communication interventions. The approach is directly linked to enabling ownership, critical thinking and mobilization of knowledge for change.